Ankle arthrodesis - Mohd Yusof, Nazri (2022)
Ankle arthrodesis is procedure to fused the tibia talar joint in patient with pain, instability or deformity and the ankle joint. When perform in the suitable patients with correct surgical technique, it will results in a good functional and painless joint. Shoe modification may be required in certain patient.